TRANSFORMASI HUKUM KELUARGA ISLAM DI INDONESIA: Telaah Pemikiran Rifyal Ka’bah - Asmaret, Desi; Koto, Alaiddin; M, Afrizal (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
This research discusses about Rifyal Ka'bah’s idea on the transformation of Islamic family law to become the national law. This research focuses on how does Rifyal Ka’bah formulate the methods of the transformation of Islamic family law into national law? What is the influence of the idea of the transformation to the development of Islamic legal thought in Indonesia? This research is a type library research with qualitative descriptive analysis.This research argues that Rifyal Ka’bah believes that gradual transformation of Islamic family law to become National law is the best way to make Islamic family law going down to earth. This can be performed by the issuance of judge's decision with a fair and consistent attitude. From the perspective of theoretical Islamic law, it is very useful to use of ra'y and urf as sources of Islamic law after al-Qur’an, Hadis, and Ijma’ through the process of ijtihad jamā'i and tarjih. Rifyal Ka'bah has given significant influences to the emergence of various efforts of Islamic jurists in revising laws and regulations in accordance with the substance contained in Islamic law, jurisprudence guided by judges throughout Indonesia and changes in the mindset judges to apply the theory of diyāni and qaḍā 'i.Penelitian ini mengkaji pemikiran Rifyal Ka’bah dalam mentransformasikan hukum keluarga Islam menjadi hukum Nasional. Permasalahan utamanya: Bagaimana pemikiran dan sikap Rifyal tentang transformasi hukum keluarga Islam? Apakah metode penggalian hukum yang diterapkan Rifyal? Bagaimana posisi dan pengaruh pemikiran Rifyal dalam khazanah pemikiran hukum Islam di Indonesia? Penelitian bertujuan mewujudkan harmonisasi syari’at Islam dengan hukum Nasional. Penelitian ini menggunakan metode penelitian pustaka dengan analisis deskriptif kualitatif. Temuan penelitian: Pertama, Pemikiran dan sikap Rifyal Ka'bah tentang transformasi hukum keluarga di Indonesia adalah mengubah fikih munakahat menjadi hukum Nasional, yakni memasukkan substansinya berangsur-angsur melalui putusan hakim dengan sikap adil dan konsisten. Kedua, metode penggalian hukum Rifyal Ka'bah adalah pengembangan metodologi uṣul al-fiqh dengan menempatkan ra'yu dan urf sebagai sumber hukum Islam setelah Alquran, hadits dan Ijma’ melalui metode ijtihad jamā'i dan tarjih. Ketiga, Pemikiran Rifyal Ka'bah mempengaruhi berbagai upaya para ahli hukum Islam dalam merevisi hukum dan peraturan sesuai dengan substansi hukum Islam, yurisprudensi yang dipedomani oleh hakim seluruh Indonesia, dan perubahan mindset hakim untuk menerapkan teori diyāni dan qaḍā'i.